Does Tourism Development Contribute to Human Development in Africa? (2017)
The literature has been awash with alternative explanations for structural and economic transformation in more recent years. Growth drivers are myriad in empirical depictions and enquiries into deeper causal relationships have preoccupied development discourse. Particularly, the contributory role of tourism development in job creation, thereby increasing the standard of living, national output, foreign exchange earnings and revenue to the government through taxation have been brought into sharper view by extant studies. To this end, the developmental gains arising from expansion of activities in the tourism industry has equally blossomed. This is particularly the case in Africa owing on one hand to the high influx of tourists into the continent as well as the relative size of tourism receipts to gross domestic product (GDP) for key continental destinations on the other hand. Hence, the central question is how has tourism development influenced overall economic development in the African context? To pursue this train of inquisition, this study examined the effect of tourism development on human capital development in Africa. Precisely, the study uncovered the role of tourism in influencing human capital development using data on a panel of twenty-five (25) African countries covering the period from 1998 to 2014. System General Moment Method (GMM) estimation techniques was deployed in the study in a requisite bid to account for endogeneity and unlike previous work human capital is decomposed into education and health to facilitate clearer understanding on the specificity of the impacts of tourism development in the economy. The study findings showed that tourism development vis-à-vis tourist arrival and tourism receipt had positive and significant effect on human capital development in Africa. This result is found to be robust to the choice of human capital indicator albeit with certain variations contingent on model specification. Thus, appropriate policies that will make the continent's tourist sites attractive to tourists need to be implemented.